A case study on predicting corporate performance from organizational culture / Lat Azla Mohd Tajuddin - Mohd Tajuddin, Lat Azla (Faculty of Business and Management, 1995)
This project paper is mainly to study relationship between corporate culture and corporate performance for the companies listed under the plantation sector on the Kuala Lumpur Stock exchange (KLSE).